2020
DOI: 10.1111/deci.12467
|View full text |Cite
|
Sign up to set email alerts
|

Operational Risks and Firm Market Performance: Evidence from China*

Abstract: This study investigates how different operational risks impact firm stock market performance. By using a sample of 762 operational risk events published by 543 listed Chinese firms over the period of 2010–2017, we document an overall significantly negative market reaction to operational risks. Specifically, we find that the stock market reaction differs across operational risk types. Man‐made operational risk and disruption operational risk events are associated with greater negative market reaction than natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…One of these major risks that business entities face is an operational risk (Engle, 2009;Bai, Gao & Sarkis, 2021), which is inherent in every human activity and ascends from activities such as acts of fraud, errors, negligence, violations, technological failure events, process deficiencies, system flaws, acts of terrorists and vandalism, as well as natural disasters like floods, earthquakes etc. (Hussain & Shafi, 2014).…”
Section: Insights Into Regional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these major risks that business entities face is an operational risk (Engle, 2009;Bai, Gao & Sarkis, 2021), which is inherent in every human activity and ascends from activities such as acts of fraud, errors, negligence, violations, technological failure events, process deficiencies, system flaws, acts of terrorists and vandalism, as well as natural disasters like floods, earthquakes etc. (Hussain & Shafi, 2014).…”
Section: Insights Into Regional Developmentmentioning
confidence: 99%
“…One of the challenges that face manufacturing companies is operational risks. Operational risks are most prevalent in the manufacturing and mining industries (Qeke & Dubihlela, 2018;Bai, Gao & Sarkis, 2021). Manufacturing businesses encounter undesirable events and unwanted setbacks such as machine breakdowns, material shortages, accidents, and absenteeism that make the system unreliable and inconsistent (Islam & Tedford, 2012;Islam, Tedford & Haemmerle, 2008).…”
Section: Smes In the Manufacturing Sectormentioning
confidence: 99%
“…Focused more on description than prescription, it suggests that disasters damage production facilities and force retail operations to close, putting them at a disadvantage relative to firms not experiencing disaster; however, this disadvantage dissipates as surviving firms recover (Cainelli et al 2018;Cole et al 2019;De Mel et al 2012;Park et al 2013;Stromberg 2007). Notably, Bai et al (2020) lament the lack of studies that test predictors of performance-based outcomes.…”
Section: Background Conceptual Model and Hypothesis Developmentmentioning
confidence: 99%
“…Shin and Lee (2019) found that generic resources improve outcomes, with cash the most useful due to its versatility. Whether disruptions are caused by a human (e.g., fires started by accident) or nature also matters, with the former associated with larger stock price declines (Bai et al 2020).…”
Section: Background Conceptual Model and Hypothesis Developmentmentioning
confidence: 99%
“…Market dynamism therefore intensifies the complexity of the organizational environment as firms need to collect more customer-and market-specific information to develop competitive strategies (Bai et al, 2021). Although these distinctive strategies are developed, firms are stratified in the same segment due to their adoption of similar strategies (Balietti & Riedl, 2021;Vadakkepatt et al, 2021).…”
Section: Market Dynamism and International Alliance Partner Diversitymentioning
confidence: 99%